The Impact of Songs on Vocabulary Acquisition by ESL Undergraduate Students - Lijiao, Cheng; Amirdabbaghian, Amin (Vivid: Journal of Language and Literature, 2024)
The purpose of this study was to investigate the impact of music on vocabulary acquisition among ESL undergraduate students at the UM School of Languages, students’ preferences for music choices, and their motivations for using music as a learning tool. By analyzing the questionnaire responses of 81 participants, the study found the following results. First, the vast majority of participants found listening to English songs helpful in learning the English language. Second, pop music was the most preferred genre of music among the participants, but rock, jazz, and rap also received a significant amount of support. A small number of participants chose other types of music. In addition, students’ motivations for using music as a learning tool mainly included singing along with songs, listening to songs repeatedly, and reading lyrics. These motivations stemmed from students’ concerns about pronunciation accuracy, vocabulary recall, and song meaning. Strengths of the study include the fact that the quantity and quality of the data were adequate and the results were well presented. However, there are some limitations of the study, such as the limitations of the study population and the subjectivity of the data. Therefore, this paper suggests further expansion of the study population, incorporation of objectivity measurement tools, exploration of the effects of different music genres, and provision of relevant training and guidance for teachers. In conclusion, the results of this study validate the effectiveness of music as a tool for vocabulary acquisition and have practical implications for promoting students’ language learning.